2011
DOI: 10.1007/s00484-011-0503-9
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of influential factors on outdoor thermal comfort in summer

Abstract: A variety of research has linked high temperature to outdoor thermal comfort in summer, but it remains unclear how outdoor meteorological environments influence people's thermal sensation in subtropical monsoon climate areas, especially in China. In order to explain the process, and to better understand the related influential factors, we conducted an extensive survey of thermally comfortable conditions in open outdoor spaces. The goal of this study was to gain an insight into the subjects' perspectives on wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 32 publications
0
40
1
2
Order By: Relevance
“…Some previous Asian urban micro-climate researchers were also very active, for instance, Ng et al [11] investigated urban human thermal comfort in Hong Kong, Lin and Hwang [37,38] in Taiwan, Thorsson et al [21] and Knez et al [39] investigated Japanese urban public places, Jeong et al [40] conducted similar studies in Korea; and for Mainland China, there were related investigations in Nanjing [41], Wuhan [42,43] and Tianjin [44].…”
Section: Introductionmentioning
confidence: 96%
“…Some previous Asian urban micro-climate researchers were also very active, for instance, Ng et al [11] investigated urban human thermal comfort in Hong Kong, Lin and Hwang [37,38] in Taiwan, Thorsson et al [21] and Knez et al [39] investigated Japanese urban public places, Jeong et al [40] conducted similar studies in Korea; and for Mainland China, there were related investigations in Nanjing [41], Wuhan [42,43] and Tianjin [44].…”
Section: Introductionmentioning
confidence: 96%
“…Solar radiation, atmospheric pressure, maximum temperature, wind speed and relative humidity determine the outdoor comfort level, as Yin (2011) suggested that a strong relationship may exist between microclimatic and comfort conditions. In the present work, biometeorological observations were carried out on Hungarian Grey cattle.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of environmental factors, such as temperature, humidity and wind speed, which all impact on the animals, need to be examined in a broad context (Anda et al, 2010;Lovelock, 2010;Yin and Zheng, 2011). Previous zoometeorological observations pointed out that grazing cattle react differently to various weather conditions (Malechek and Smith, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The feet, as the distal extremities of human body, consist of massive capillaries [12], and therefore, local thermal exposure of foot has a significant impact on overall human thermal responses [13]. Since thermal responses of human body are difficult to be reconstructed, researchers have performed a great number of studies to find how occupants feel and adapt to inhomogeneous and dynamic environments [14], including experimental investigations carried out in public buildings [15,16], vehicles, and outdoors [17,18], which aim to explore relations between human thermal responses and thermal environment parameters. In addition, the thermal comfort due to local thermal exposure has been extensively investigated in the air environment based on heat transfer process [19][20][21], psychology [22][23][24][25] and physiology [26][27][28].…”
Section: Introductionmentioning
confidence: 99%